Patterns of U.S. migration from a Haitian sending community - Lundy, Garvey F. (2007)
Provides a general description of Haitian households involved in both internal and external migration. Gives an insight into the social context that facilitates migration to the United States. Provides also, a snapshot of the experiences of Haitian migrants in the United States by comparing their circumstances to that of non-migrants.